A Negotiation with Reality: The Discursive Elements of the Dramatised Dissemination Documentary: My Octopus Teacher: a Case Study - Muñoz Gallego, Almudena; Quintino de Sousa, Pedro (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The documentary genre is one of the audiovisual mechanisms with the greatest media efficiency in the transmission of reality. However, depending on the nature of the story, the construction of the textual and audiovisual discourse is altered. In this article, we consider the following questions: Is the documentary a format that is faithful to reality? What modifications does the discourse undergo so that the story is enhanced? To go deeper into this aspect, we intend to analyse the different elements that make up the documentary discourse in its transition from reality to fictionalised narrative. To this end, an inspection of the environmental dissemination documentary My Octopus Teacher (Netflix, 2020) will be carried out. An audiovisual proposal in which the coexistence between human and animal life turns environmental dissemination into a powerful instrument for transmitting scientific knowledge.